KARAKTERISTIK PASIEN SINDROM GUILLAIN-BARRÉ DI RSUP DR. M. DJAMIL PADANG TAHUN 2020-2023 - Masra, Salwa Atsilah (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Guillain-Barré syndrome (GBS) is a post-infectious autoimmune disease that attacks components of the peripheral nervous system and presents with the distinctive clinical feature of acute ascending flaccid paralysis. The incidence of GBS varies globally, with a notable increase observed over the past two decades. The prevalence of GBS in Indonesia, particularly in West Sumatra, has not been fully documented. Aim: To elucidate the characteristics of GBS patients at RSUP Dr. M. Djamil Padang in 2020-2023. Methods: This study utilizing the total sampling technique. It relies on secondary data in the form of medical records obtained from RSUP. Dr. M. Djamil Padang in 2020-2023. The study encompasses 52 samples that meet the inclusion criteria. Results: Predominantly GBS affects individuals aged ≥ 18 years (65%), with a male preponderance (65%). The median onset of the disease is 8 days, ranging from 1 to 56 days, while the nadir in most patients was reached within ≤ 14 days (81%). More than half of the patients had a history of preceding infections (60%). Most of the patients had clinical symptoms include weakness in both extremities (79%), hyporeflexia (65%), and negative sensory symptoms (50%). Most of them do not exhibit autonomic dysfunction (81%) or cranial nerve dysfunction (63%). Over half of the patients show cytoalbuminologic dissociation (56%). More than half of the patients were identified as AMSAN subtype (56%), with over half of the patients experiencing a severity score of 4 (54%). Corticosteroids were the primary therapeutic regimen received by most of the patients (54%). Discussion: The outcomes of this study contribute valuable information and support enhanced diagnostic and management efforts. Keywords: Characteristics, Guillain-Barré Syndrome, GBS